2021
DOI: 10.3390/ijms22137038
|View full text |Cite
|
Sign up to set email alerts
|

Functional Validation of cas9/GuideRNA Constructs for Site-Directed Mutagenesis of Triticale ABA8′OH1 loci

Abstract: Cas endonuclease-mediated genome editing provides a long-awaited molecular biological approach to the modification of predefined genomic target sequences in living organisms. Although cas9/guide (g)RNA constructs are straightforward to assemble and can be customized to target virtually any site in the plant genome, the implementation of this technology can be cumbersome, especially in species like triticale that are difficult to transform, for which only limited genome information is available and/or which car… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…In the groups with puromycin selection, the T7E1 assay detected 12.9–72.1% indels, which was similar to the results of the previous reports ( Abu-Bonsrah et al, 2016 ; Bai et al, 2016 ; Antonova et al, 2018 ). The performance of T7E1 may be impacted by the length and identity of base pair mismatches, flanking sequence, secondary structure, and relative abundance of mutant sequence ( Vouillot et al, 2015 ; Michalski et al, 2021 ). Several reports showed that the indel frequencies of T7E1 assays were significantly less than NGS assays when the amount of edited DNA is a trace or abundant ( Santhakumar et al, 2018 ; Sentmanat et al, 2018 ; Jin et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the groups with puromycin selection, the T7E1 assay detected 12.9–72.1% indels, which was similar to the results of the previous reports ( Abu-Bonsrah et al, 2016 ; Bai et al, 2016 ; Antonova et al, 2018 ). The performance of T7E1 may be impacted by the length and identity of base pair mismatches, flanking sequence, secondary structure, and relative abundance of mutant sequence ( Vouillot et al, 2015 ; Michalski et al, 2021 ). Several reports showed that the indel frequencies of T7E1 assays were significantly less than NGS assays when the amount of edited DNA is a trace or abundant ( Santhakumar et al, 2018 ; Sentmanat et al, 2018 ; Jin et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Michalski et al. (2021) augmented the Cas9 gene with monocot codon‐optimized human THREE PRIME REPAIR EXONUCLEASE 2 (TREX2) sequence to improve nuclease activity in hexaploid triticale ( x Triticosecale ; 2 n = 6 x = 42) protoplasts and observed increases in mutagenesis efficiency of up to 19‐fold for gRNAs expressed from TREX2‐enhanced vectors.…”
Section: Factors Impacting Multiallelic Editing Efficiency In Polyploidsmentioning
confidence: 99%
“…Co-editing of The Plant Genome multiple alleles was identified in 54% of potato transformants containing the dMac3-Cas9 system, while only 7% of transformants containing the ADH enhancer carried mutations in multiple target alleles (Kusano et al, 2018). Michalski et al (2021) augmented the Cas9 gene with monocot codon-optimized human THREE PRIME REPAIR EXONU-CLEASE 2 (TREX2) sequence to improve nuclease activity in hexaploid triticale (x Triticosecale; 2n = 6x = 42) protoplasts and observed increases in mutagenesis efficiency of up to 19-fold for gRNAs expressed from TREX2-enhanced vectors.…”
Section: Optimization Of Cas Expression and Activitymentioning
confidence: 99%
“…In a short time, MAH 1590 was registered by Dr. Bogusław Łapiński as 'Bogo, ' a new high-yielding winter triticale variety. 'Bogo' has been successfully grown for many years in Poland, and aer 30 years since our discovery, it continues to serve as a model genotype used in studies on in vitro plant regeneration and transformation of triticale (Hensel et al, 2012;Michalski et al, 2021;Oleszczuk et al, 2004;Sowa et al, 2005).…”
Section: Somatic Embryogenesis As a Prerequisite For Genetic Modifica...mentioning
confidence: 99%
“…Being aware of all these challenges, we continuously master genomic techniques through scientific research and must be ready to produce improved and safe breeding materials, now by optimizing the recent CRISPR/Cas9 method (Michalski et al, 2021).…”
Section: New Genomic Techniques -Legal Problems and Challenges For Id...mentioning
confidence: 99%